Reflections on community safety: the ongoing precarity of women's lives. Issue 4 (November 2018) - Walklate, Sandra
Abstract In 2007 Jayne Mooney observed that violence against women was a public anathema and a private commonplace all at the same time. In the decade since this observation was made it would not be hard to conclude that the situation remains the same despite the increasing public policy profile afforded to such violence(s). The purpose of this paper is to consider how and why such forceful observations can still be made and it will do so by reflecting on five inter-connected ongoing tensions for the community safety agenda in addressing violence against women. These tensions are: epistemic (who can know what); methodological (how things, like violence against women, can be known); conceptual (how to make sense of what we think we know); saliency (what variables count and when); policy (what can be done in the light of the foregoing issues); and global (the Northern bias endemic in such policies). The paper will suggest that only when debates on community safety fully embrace the implications of these issues will effective in-roads be made into understanding and improving the ongoing precarity of women's lives.